Consistent Law Enforcement Creates An Anti-Gambling Legal Culture - Hardum, Siprianus Edi (Dinasti Research, 2026)
One of the challenges of the current Indonesian State is the crime of gambling. Offline and online gambling does not have a positive impact on individuals, society and the country at all. Precisely the negative impact that arises, among others, first, the impact on individuals and families, namely gambling makes poor. Playing gambling, both online and offline, makes a person and his family economically destitute. The group of people who fall into gambling is a group of people who are classified as poor and low-income. They are already poor, they are playing gambling, they are getting poorer. In addition to economic losses for the gambler, online gambling is also addictive: Online gambling is addictive. The person involved often finds it difficult to stop even though they have already suffered a loss. their money to scammers. The next impact for the individual is mental disorders. Anxiety, depression, and severe stress are often experienced by gamblers who lose or feel guilty. The impact on the family is the rift in the household. Online gambling can cause arguments, loss of trust, and divorce. Family money can be spent on gambling, leading to financial hardship and unmet basic needs. In extreme cases, children can experience neglect due to parents who are too focused or addicted to gambling. Impact on Society. Crime rates are increasing: Implications for the State. The state has to spend huge costs on law enforcement, rehabilitation, and handling the social impact of online gambling. Therefore, this article offers solutions to prevent and eradicate gambling.